Comparative buckling analysis of laminated composite plates with various shapes of hole. (2021) - Kumar, Rahul; Lal, Achchhe; Sutaria, B.M.
Abstract: A comparative buckling analysis of a graphite/epoxy laminated composite plate with a hole of various shapes having constant cutout area is carried out using finite element based first-order shear deformation theory (FSDT) in the present study. A MATLAB program is developed and used for parametric studies of plates with a hole under uniaxial in-plane compressive load. Four noded isoperimetric quadrilateral element having twenty unknowns are considered for discretization of the plate. The efficiency of the program is verified by comparing the present and published results and found good agreement between them. The effect of different parameters like thickness ratio, stacking sequence, fiber orientation, modulus ratio, along with the shape of the hole on normalized critical buckling load (NCBL) is investigated.